The Impact Of Islamic Finance, Economic Growth, And Globalization On CO2 Emissions - Yasirwan; Imsar; Muhammad Ikhsan Harahap (Jurnal Ekonomi, 2024)
This paper examines the impact of Islamic finance, economic growth, and globalization (economic, social, political, and overall aspects) on carbon dioxide emissions in 4 countries for the period 2015-2020. Employing the System GMM estimation method, which fulfills criteria for model unbiasedness, validity, and consistency. Findings reveal that Islamic finance, economic growth, and globalization simultaneously contribute to increasing and decreasing carbon dioxide emissions with a significance level of 0.010. Partially, Islamic finance and globalization’s overall aspect in short or long term contribute to a decrease in carbon dioxide emissions with a significance level of 0.010. Meanwhile, economic growth and globalization in economic, social, or political aspects in short or long term contribute to an increase in carbon dioxide emissions with a significance level of 0.010. This scientific article provides a new contribution to the research results that have been obtained with a significance level of 0.010 or 99 per cent confidence level.